Taxes, Subsidies, and Employment - Ahluwalia, Montek S. (Quarterly Journal of Economics, 1973)
I. The equilibrium of a surplus labor economy, 394. — II. The role of commodity taxation, 398. — III. The role of general factor taxation subsidy, 401. — IV. Factor taxation subsidy in one industry, 403. — V. Conclusions, 407.